Relook at the silent victim: examining open space loss due to right of way encroachment in Sokoto, Nigeria - Bello , Ashiru; Abdulghafar, Maszura (Zes Rokman Resources, 2016)

(untitled)
Urban activities and activity areas usually wish to have good neighbours that are complimentary to their sustainable functionality. Unfortunately however, open spaces, particularly in form of right of ways (ROW) are not lucky enough to have good neighbours where urban governance is poorly conceived and pursued. Linking sustainability in urban planning and design with participatory urban governance, this paper examined the challenges of participatory city planning and management as well as open-space loss to urban development (which according to UN Habitat contributes 50% of global greenhouse emissions). It is an extension of an earlier study which focused on the spill-over effects of right of way encroachments through construction of mosques on different categories of urban roads in Sokoto metropolis, North West Nigeria. The earlier study focused on the trend of such encroachments from 2005 to 2010. This study first categorized the different urban road hierarchies in the city and examined the occurrence of the phenomenon as well as observed and potential implications on adjacent uses, using cross-sections, interviews and time series images. Between 2011 and 2015, the study revealed that the phenomenon of ROW encroachment is sustained and there is a 15.6m increase in the amount of urban road right of way that is lost at the point of encroachment at the Sultan Abubakar road and 7m at the third location that is Sakaba road as compared to the 2005-2010 observations. Furthermore, in addition to the weakness of urban management institutions, low level of inclusiveness has been observed from the community regarding the use of road right of ways and consequences of its encroachment which is reflected in the residents’ readiness to encroach should an opportunity becomes available. Poor participation particularly in plans implementation is therefore evident. Similarly, as a by-product of the socio cultural and economic context, this phenomenon (although may require a radical development control approach to correct) can be mitigated through adoption of proper participatory techniques in urban planning and development.